Zastopnik pravic oseb na področju duševnega zdravja - Kobal, Klavdija (Obzornik zdravstvene nege, 2010)
A political decision is often needed to introduce and achieve a reform in a specific field. In the realm of mental health, such a decision has been demonstrated by the adoption of the Mental Health Act, which covers the assessment, treatment and rights of people with a mental health condition. The present article addresses the role of a representative of human rights in the field of mental health, their legal competence along with ethical dilemmas when intervening in certain real-life situations.
Keywords: bolniki; človekove pravice; duševno zdravje; hospitalizacija; human rights; mental health; varovalni ukrepi; zastopniki